Building strong nations improving governability and public management - Vigoda-Gadot, Eran (Ashgate Pub., 2009)
In the face of global challenges and changes one major dilemma looms large for citizens and leaders worldwide: How can we ensure that our countries address these challenges successfully? This book demonstrates that the answer can be found in a better match between the nature of modern bureaucracy and the spirit of modern democracy.